2017
DOI: 10.1158/0008-5472.can-16-2409
|View full text |Cite
|
Sign up to set email alerts
|

E3 Ubiquitin Ligase UBR5 Drives the Growth and Metastasis of Triple-Negative Breast Cancer

Abstract: Patients with triple-negative breast cancers (TNBC) are at high risk for recurrence and metastasis at an early time despite standard treatment, underscoring the need for novel therapeutic modalities. Here, we report for the first time a distinctive and profound role of the E3 ubiquitin ligase UBR5 in the growth and metastasis of TNBC. An analysis of primary TNBC specimen by whole-exon sequencing revealed strong gene amplifications of UBR5 associated with the disease. UBR5 overexpression in TNBC tissues was con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
114
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 105 publications
(126 citation statements)
references
References 52 publications
12
114
0
Order By: Relevance
“…TNBC is characterized by the absence of estrogen receptor (ER), progesterone receptor and human epidermal growth factor receptor type 2 (HER2) expression, which means that patients with TNBC cannot be treated with endocrine therapy or therapies targeting HER2 (2)(3)(4). Notably, conventional chemotherapy remains the principal treatment for TNBC, but is associated with a high recurrence rate (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…TNBC is characterized by the absence of estrogen receptor (ER), progesterone receptor and human epidermal growth factor receptor type 2 (HER2) expression, which means that patients with TNBC cannot be treated with endocrine therapy or therapies targeting HER2 (2)(3)(4). Notably, conventional chemotherapy remains the principal treatment for TNBC, but is associated with a high recurrence rate (5,6).…”
Section: Introductionmentioning
confidence: 99%
“…Following overnight incubation, various concentrations of the anticancer drugs epirubicin or docetaxel (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) was added into the medium and cultured for 72 h, and then the cell viability was measured by an SRB assay (34,35). Briefly, the cells were fixed with 10% trichloroacetic acid for 30 min at 4˚C and stained with 0.4% (w/v) SRB (Sigma-Aldrich; Merck KGaA, Darmstadt, Germany) in 1% acetic acid solution for 30 min.…”
Section: Cell Sensitivity To Drugs By Sulforhodamine B (Srb) Assaymentioning
confidence: 99%
“…Recently UBR5 has been shown to target substrates also through other recognition mechanisms than N-terminal recognition (Shen, Qiu et al, 2018). UBR5 is essential for mammalian development (Saunders, Hird et al, 2004), and has been linked to both protumourigenic and tumour suppressor activities (Clancy, Henderson et al, 2003, Liao, Song et al, 2017, Saunders et al, 2004. However, the mechanism by which UBR5 would promote tumour growth, and how the protumourigenic effects of UBR5 in human cancer cells (Clancy et al, 2003, can be consolidated with its suggested role as a tumour suppressor in Drosophila (Clancy et al, 2003, Saunders et al, 2004, remains as critical unanswered questions (Shearer et al, 2015).…”
Section: Introductionmentioning
confidence: 99%